EU common agricultural policy: Impacts on trade with Africa and African agricultural development - Lukas Kornher; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2020)
The impacts of European agricultural and trade policies on agricultural development and food security in Africa are analyzed in this study. The research is prompted by the pending further development of the Common Agricultural Policy (CAP) after 2020. The proposal for the new CAP is based on higher ambitions with regard to environmental protection and climate change through mandatory ecological programs and an enhanced linkage of direct payments to the greening rules. The methodological approach comprises: (i) an examination and critical review of existing studies; (ii) an analysis and assessment of agricultural trade flows between the EU and Africa as a whole and in the context of case studies on meat and milk; (iii) a systematic consultation of leading experts in European and African agricultural and trade policy on trends and impacts of the CAP; and (iv) model simulations of the effects of possible reform projects on production in and trade flows with Africa. The study finds that direct payments to EU farmers continue to account for up to 50% of total farm income in the EU, but EU spending on agricultural development in Africa is rather small in comparison. The current EU agricultural subsidy policy hampers the development of African agriculture much less than it did before export subsidies and coupled subsidy payments were largely abolished. However, these earlier effects cannot be corrected quickly because agricultural productivity depends on longstanding favorable framework conditions and long-term investments in innovation. According to the expert consultation carried out for this study, a stronger environmental and climate orientation of the CAP is considered likely and would have a dampening effect on European agricultural exports to Africa. The model simulation estimates that European food exports to Africa would decrease under the expected EU policy changes. However, this reduction in European exports would be mainly taken over by other exporters. Investments in African agricultural development should be expanded by the EU. Although African raw agricultural material exports to the EU are largely free of duties, the access of processed products to the EU market is still limited due to complicated rules of origin and social and hygiene standards for goods imported into the EU. These standards are necessary but must be more transparent. The EU should provide more support to improve standards in Africa; otherwise, the export potential of African countries cannot be fully exploited.
Keywords: F13; O13; Q1; 330; post-2020 CAP; agricultural development in Africa; EU-Africa trade